2019
DOI: 10.1177/1558944719864453
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Reoperation After Silicone Proximal Interphalangeal Joint Arthroplasty

Abstract: Background: Silicone proximal interphalangeal (PIP) joint arthroplasty has a high revision rate. It has been suggested that persistent ulnar deviation and joint instability influence the durability of PIP silicone arthroplasties. The goal of this study was to evaluate what factors are associated with reoperation after silicone PIP arthroplasty. Methods: We retrospectively evaluated all adult patients who underwent PIP silicone arthroplasty between 2002 and 2016 at one institutional system for inflammatory-, po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…However, in our study the index fingers underwent the least reoperations of all fingers. 23 Additionally, a recently published review puts the contraindication for performing arthroplasty of the index finger under discussion. They found that there is no difference in overall deformity, instability, and complication rate between long and index fingers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in our study the index fingers underwent the least reoperations of all fingers. 23 Additionally, a recently published review puts the contraindication for performing arthroplasty of the index finger under discussion. They found that there is no difference in overall deformity, instability, and complication rate between long and index fingers.…”
Section: Discussionmentioning
confidence: 99%
“…The overall reoperation rate following silicone PIP arthroplasty is 14% compared with 30% following pyrocarbon arthroplasty. 23 Besides that additional surgeries increase overall costs, based on Medicare reimbursement, the costs for a pyrocarbon PIP implant are $1,890 versus $406 for a silicone PIP implant. 24 The reason why posttraumatic arthritis was associated with reoperation is unclear, but possible explanations may be preoperative joint deformity, injury to soft tissues including the capsule, incompetent collateral ligaments, or heavier loading of the fingers compared with those with inflammatory arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…15 Disadvantages of silicon joints arthroplasty include: it is technically difficult, expensive, (cost 120 British Pounds/joint, manufactured by Osteotec Ltd, Building 81, Greenham Business Park, Newbury, Berkshire, UK RG19 6HW) not universally available and associated with a possibility of implant fracture/extrusion, infection, dislocation, silicone synovitis, extensor lag and tendency for worsening outcome in long-term. 16 , 17 Implant arthroplasty while preserving motion has an implant complication rate of 42% at 10 years and 66% at 17 years. Revision rates were 17% at 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was an overall rate of complications of 34% and a 16% rate of revision surgical procedures 21 . Another study of 114 PIP joint silicone arthroplasties also showed a high reoperation rate of 14%, with risk factors being a surgical procedure on the index finger, smoking status, non-Caucasian race, and arthroplasty performed for posttraumatic arthritis 22 .…”
Section: Hand Arthritismentioning
confidence: 99%